Petrography of exotic clasts in the soebi blanco formation, bonaire, netherlands antilles (2013)
The Paleocen e Soebi Blanco Formation in the island of Bonaire in Southeastern Caribbean has attracted the attention of geologists since 1931 when P. J. Pijpers pointed out the presence of a wide range of “foreign pebbles” in conglomerate beds. Interest was further boosted in 1986 with a Grenvillian age determined in a granulitic pebble (ca. 1150 Ma, U-Pb, TIMS, zircon) letting the authors propose an eastward translation of at least 300 km for the island of Bonaire relative to Guajira. New petrographic analysis of 21 rounded pebbles resulted in a wide span of rock types from metatrondhjemite, gneisses, metadiabase, andesitic lava and tuff, epiclastic metasedimentary, metapsamite, ultramylonitic marble, quartz arenite, conglomeratic sandstone and limestones (wackstonte, packstone). The variety of rock types support a combined arc-continental source region, a condition that was met in the northwestern corner of South America during Paleocene times.